Paradise lost ebook - Milton, John (Duke Classics, 2012)
Paradise Lost is one of the most epic, complex theological works to date. Milton's masterpiece in blank verse tells the story of the fall from grace. His protagonist is often read as Satan, who rebels against the omnipotent God, though he cannot win. Milton expresses the paradox of free will within the creation of an all-knowing God.